Effect of Mixing Sequence on Properties and Fibre Dispersion of Glass Fibre Reinforced Cementitious Mortar - Affif M. Sapawi; Abraham H. Bernard; Ahmad N. Rizalman; S. M. Iqbal S. Zainal; Guan Lin; Zhao Danwei; Rosalam Sarbatly (Salehan Institute of Higher Education, 2026)
Cementitious composites play a vital role in construction due to their favourable strength, durability, and workability. Nonetheless, these materials are susceptible to cracking. Although incorporating glass fibres has improved mechanical properties, achieving uniform fibre dispersion remains a significant challenge. The objective of this study was to examine the effect of mixing sequence on the engineering properties and fibre dispersion of glass fibre–reinforced cementitious mortars (GFRCMs). There were four mixing sequences including: four mixing sequences for glass fibre-reinforced cementitious mortars (GFRCMs): (i) S1(fibres were incorporated into dry mortar mixtures), (ii) S2 (fibres were incorporated into fresh mortar mixtures), (iii) S3 (fibres added alongside gradual water addition, (iv) S4 (fibres were included during incremental water additions). This study examined various properties in accordance with the American Society for Testing and Materials (ASTM) standard test methods, including compressive strength, hardened density, setting time, flowability, and flexural strength. Scanning electron microscopy and fibre-distance analysis were also employed to evaluate the fibre dispersion of the specimens. The results indicate that fibre addition reduced the flowability and shortened the setting time of the mortar, whereas improvements in hardened properties depended strongly on dispersion quality. The most uniform fibre distribution was observed in S4 (β = 0.685), resulting in maximum compressive and flexural strengths of 15.88 MPa and 10.39 MPa, respectively, at 28 days. The strong correlations observed between density and porosity (R² = 0.8035) and between density and compressive strength (R² = 0.8184) indicate that reduced void content and enhanced fibre distribution are key contributors to the observed performance gains. This work establishes relationships among mixing sequence, fibre dispersion, and key engineering properties to guide fibre-mixing processes in cementitious composites.